Optimizing low complexity encoding method for systematic polar code - Linhua MA; Shiping LIU; Xing HU; Tianyu HUANG; Bin XU (Tongxin xuebao)
In order to solve the delay caused by step-by-step calculation and the computational complexity caused by iterative “exclusive-or” computation during the encoding process,a dimensionality reduction strategy was proposed and defined.Based on this,system polarization code parallel coding algorithm for cracking strategy was proposed.Simulation and computational complexity analysis were carried out on AWGN channel.The results show that the coding gain of the above algorithm is slightly better than the traditional one or almost the same,but the computational complexity is up to 80.92%,which is more suitable for hardware implementation and engineering application.It is more suitable for hardware implementation and has a certain practical value.